Literature Review; Analisis Karakteristik Perawat Yang Dibutuhkan Guna Menunjang Tercapainya Kepuasan Pasien - Taufan Agung Prasetyo; dedi irawandi; Dya Sustrami (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2021)
Introduction: Nurses in a health institution are important. Nurses are healthworkers who have the most direct interactions with patients, so the figure of agood nurse is certainly expected by patients or their families. In this case, theassessment of the figure of a good nurse is not only seen from her scientificability to provide nursing care, but also must pay attention to other factors,such as friendliness, appearance, and ways of communicating. Objectives: Thepurpose of this review literature is to analyze the characteristics of nursesneeded to support patient satisfaction. Methods: In writing this literaturereview, using the method of searching literature from international articlesusing the ScienceDirect, Goggle Scholar, and ProQuest databases. An initialsearch using keywords: "Nurse service and patient satisfaction" resulted in26,008 international articles from 2020, 2021, and 2020 that match theinclusion criteria. Results: The results of the literature review show that thisempathy factor can be found in 11 of the 14 articles studied. The next dominantfactor found in the 6 articles was the ability to establish good relationshipswith patients, reliability, and communication. Meanwhile, the responsivenessand assurance factors were not dominant factors respectively. Conclusions: The conclusion is that there are several characteristics of nurses that affectpatient satisfaction, namely: the ability of nurses to have good relationshipswith patients, responsiveness, reliability, empathy, able to communicate well, andable to provide assurance. From the existing articles, it can be seen thatempathy is a dominant factor in influencing patient satisfaction